2021
DOI: 10.1055/a-1562-1893
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19-Pandemie: Angsterleben von niedergelassenen und Krankenhaus-Psychiatern

Abstract: Zusammenfassung Hintergrund Bisher gibt es keine Studien, die das Pandemie bedingte Belastungserleben von stationär im Vergleich zu ambulant tätigen Psychiatern untersucht hat. Es soll deshalb das Ausmaß der Covid-19-Exposition, die Angst, das Belastungserleben und die Bewältigungsmöglichkeiten bei niedergelassenen Psychiatern im Vergleich zu Ärzten in psychiatrischen und psychosomatischen Kliniken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The higher anxiety level in female urologists during the fourth wave is in line with the results of a German and French survey that evaluated mental health issues in healthcare workers during the beginning of the pandemic (8,27). However, a previous analysis examining the pandemic-related stress experience of psychiatrists revealed that anxiety was dependent on feeling restricted (OR = 5.52) and risk of infection (OR = 5.74) but not on gender (28). The physical and psychological burden healthcare workers experienced during the COVID-19 pandemic is high, as the prevalence of burnout among physicians was nearly 60% (13).…”
Section: Discussionsupporting
confidence: 76%
“…The higher anxiety level in female urologists during the fourth wave is in line with the results of a German and French survey that evaluated mental health issues in healthcare workers during the beginning of the pandemic (8,27). However, a previous analysis examining the pandemic-related stress experience of psychiatrists revealed that anxiety was dependent on feeling restricted (OR = 5.52) and risk of infection (OR = 5.74) but not on gender (28). The physical and psychological burden healthcare workers experienced during the COVID-19 pandemic is high, as the prevalence of burnout among physicians was nearly 60% (13).…”
Section: Discussionsupporting
confidence: 76%
“…Following the outbreak of COVID-19, many Chinese doctors joined the frontline work in the fight against COVID-19. Doctors who took part in the frontline work against COVID-19 had a heavier workload and burden and showed higher rates of anxiety (Uyaroğlu et al, 2020;Mattila et al, 2021;Bohlken et al, 2022) and depression (Yigitoglu et al, 2021;Zhang et al, 2021b) compared to their counterparts who did not assume such responsibilities. Thus, participating in the COVID-19 frontline work is an important factor leading to an increase in doctors' turnover intention.…”
Section: Association Of Turnover Intention With Participating In Fron...mentioning
confidence: 99%